Bile acid metabolic remodeling induced by foodborne contaminants: Mechanistic interfaces and implications for food safety risk assessment - Mengmeng Chen; Jing Cao; Shiyao Fu; Ying Han; Jianping Chen; Xin Yang; Jing Wang (Trends in Food Science & Technology, 2026)

Lambda-cyhalothrin exposure disrupts microbiota-associated bile acid metabolism and enterohepatic feedback in mice - Mengmeng Chen; Jing Cao; Shiyao Fu; Ying Han; Weijia Zheng; Jianping Chen; Xin Yang; Jing Wang (Environmental Pollution, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

An interpretable generative learning-based tri-objective optimization framework for tidal turbine hydrofoil design - Longyan Wang; Yu Fang; Xuanjie Zhu; Tianshun Xia; Jian Xu; Jianping Yuan; Yanxia Fu (Ocean Engineering, 2026)

Root oxygen governs dryland ecosystem stability - Dongliang Han; Lei Ding; Guolong Zhang; Jianping Huang; Li Fu; Ming Peng; Changyu Li; Xiaoyue Liu (Plant and Soil, 2026)

A multimodal prediction model for brain hematoma expansion based on deep neural network with transformer-driven collaborative attention fusion - Nanxu Tao; Jianping Chen; Hongjie Wu; Jiaqi Dai; Tao Zhong; Chenyang Song; Ye Wang; Yanming Chen; Qiming Fu (Medical & Biological Engineering & Computing, 2026)

Double burden: Synergistic effects of menopause and obesity on high paraben exposure-induced relative androgen predominance in women - Chao Yu; Gulijiazi Yeerkenbieke; Jianping Qian; Zhenghao Wu; Wei Yao; Jian Xiao; Jie Chen; Jianfa Gao; Xiaofang Fu; Xiqing Li (Environmental Pollution, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Construction of Kongyu 131 mutant library provides genetic resources for rice functional genomics and germplasm improvement - Tingting Xu; Qun Yang; Ran Li; Jianping Wang; Zhishan Luo; Daoyong Gong; Leihao Weng; Xiaoshan Huang; Debao Fu; Jing Li (Plant Science, 2026)

Will the arid and semi-arid regions of Northwest China become wetter under stabilized 1.5 °C and 2.0 °C warming futures? - Mi Zhang; Shuangshuang Wang; Yinqi Huang; Yifan Dong; Shuyu Wang; Jianping Tang; Congbin Fu (Climate Dynamics, 2026)

Engineering optimization of food waste treatment via anaerobic digestion: Building causal machine learning networks for comprehensive analysis - Fangyun Wang; Yi Zhang; Jianfeng Peng; Yu Fu; Hao Wan; Jinling He; Jianping Su; Yanjuan Lu; Yeqing Li (Journal of Cleaner Production, 2026)

Graph-based visual analysis for HVAC system anomaly detection - Tianyuan Cao; Yunzhe Wang; Qiming Fu; You Lu; Jianping Chen; Yushi Li; Chengtao Ji (Energy and Buildings, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

Influence of natural fracture zones on hydraulic fracture propagation and proppant transport in tight sandstone reservoirs - Shuwen Hou; Zhaozhong Yang; Liangping Yi; Dongrui Fu; Xiaogang Li; Jianping Liu; Duo Yi (Geomechanics for Energy and the Environment, 2025)

A novel multimodal data fusion neural network for predicting the crack paths in reservoir rocks - Lei Peng; Mingyao Li; Tianyu Fu; Mangu Hu; Dejun Liu; Jena Jeong; Jianping Zuo (Computers and Geotechnics, 2025)

Alleviating effect of α-lipoic acid on copper-induced oxidative stress and lipid metabolism disorders in swamp eel (Monopterus albus) - Miao He; Chuanqi Yu; Jianping Fu; Ximei Liang; Hui Wang; Chenhao Niu; Kexin Xiong; Lili Wei (Fish Physiology and Biochemistry, 2025)

On the perturbation potential energy in the synergistic effect of ENSO and South China Sea summer monsoon on the Indian Ocean dipole development - Yazhou Zhang; Yulian Fu; Bin Zuo; Jianping Li; Yina Diao; Ting Liu; Xin Qi; Haili Wang (Climate Dynamics, 2025)

Entropy-phase synergy enables stable and high-rate layered oxide cathodes for sodium-ion batteries - Xingyue Yang; Mengfei Du; Jiali Fu; Yi Yang; Zhuo Xiong; Weiyue Li; Liangzhi Li; Jianping Long; Rui Li; Jian Chen; Anjun Hu (Chemical Engineering Journal, 2025)

External and internal controls on decadal precipitation variability over North America - Xiaolu Fan; Jianping Huang; Yongkun Xie; Wenmin Wei; Yu Ren; Yihui Xu; Ming Peng; Li Fu (Climate Dynamics, 2025)

Spatiotemporal evolution and factors influencing energy system resilience in China under the dual carbon target - Lingna Liu; Siyu Yao; Jianping Ge; Tongrong Fu; Yong Yan (Journal of Cleaner Production, 2025)

Achieving underpotential Mn deposition chemistry via hydrated eutectic electrolytes for aqueous manganese metal batteries - Quanhuan Yao; Linyang Li; Xue Chen; Shenghui Zhang; He Zhang; Yujie Fu; Cong Tian; Guilong Yan; Anjun Hu; Liujun Cao; Jianping Long (Chemical Engineering Journal, 2025)

Coordinating red line policies with water consumption caps in China’s drylands - Bingfang Wu; Zonghan Ma; Xiaoming Feng; Hongwei Zeng; Si Gou; Haitao Li; Jianping Huang; Bojie Fu (Science Bulletin, 2025)

Abrupt loss of species richness caused by ecosystem transition - Li Fu; Jianping Huang; Guolong Zhang; Dongliang Han; Lei Ding; Yun Wei; Xiaoyue Liu; Changyu Li; Haipeng Yu (Science Bulletin, 2025)

Silent soils have been awakened by climate change - Dongliang Han; Jianping Huang; Xiaoyue Liu; Li Fu; Lei Ding; Guolong Zhang; Changyu Li; Fan Yang; Jinsen Shi; Beidou Zhang (CATENA, 2025)

Oxidative stress and mitochondrial dysfunctions induced by cyanobacterial microcystin-LR in primary grass carp hepatocytes - Miao He; Hui Wang; Jianping Fu; Jiming Ruan; Fugui Li; Ximei Liang; Lili Wei (Aquatic Toxicology, 2025)

sVEGFR3 alleviates myocardial ischemia/reperfusion injury through regulating mitochondrial homeostasis and immune cell infiltration - Liqun Shang; Yuanhan Ao; Xiaolin Huang; Huawei Wu; Kangni Feng; Junjie Wang; Yuan Yue; Zhuoming Zhou; Quan Liu; Huayang Li; Guangguo Fu; Kaizheng Liu; et al. (Apoptosis, 2025)

Electrically responsive photonic crystals with highly sensitive response and low power consumption for color displays - Qianqian Fu; Yanxuan Zhao; Wenyuan Yu; Jianping Ge (Chemical Engineering Journal, 2025)

High-efficiency microplastic removal in water treatment based on short flow control of hydrocyclone: Mechanism and performance - Tong Zhang; Jianping Li; Danhui Yang; Ziming Wang; Wei Zhao; Pengbo Fu; Hualin Wang (Water Research, 2024)

Hydrocyclone-induced classification reduction and spin desorption of contaminated soil remediation with heavy metal and organics - Yi Liu; Jiahui Ren; Kai Ma; Jianping Li; Pengbo Fu; Kuangfei Lin; Hualin Wang (Journal of Hazardous Materials, 2024)

A sustainable machining method with high efficiency, high quality and low wear - electric arc electrochemical composite machining - Shengsheng Zhang; Jianping Zhou; Yinan Zhao; Guoyu Hu; Fei Fu; Lizhong Wang; Yan Xu (Journal of Cleaner Production, 2024)

Experimental study on seismic behavior of reinforced concrete exterior beam-column joints under varying axial load - Xingyu Su; Hong Yang; Qingpei Liu; Xinjun Wang; Jianping Fu (Engineering Structures, 2024)

EMR-YOLO: A Study of Efficient Maritime Rescue Identification Algorithms - Jun Zhang; Yiming Hua; Luya Chen; Li Li; Xudong Shen; Wei Shi; Shuai Wu; Yunfan Fu; Chunfeng Lv; Jianping Zhu (Journal of Marine Science and Engineering, 2024)
Accurate target identification of UAV (Unmanned Aerial Vehicle)-captured images is a prerequisite for maritime rescue and maritime surveillance. However, UAV-captured images pose several challenges, such as complex maritime backgrounds, tiny targets, and crowded scenes. To reduce the impact of these challenges on target recognition, we propose an efficient maritime rescue network (EMR-YOLO) for recognizing images captured by UAVs. In the proposed network, the DRC2f (Dilated Reparam-based Channel-to-Pixel) module is first designed by the Dilated Reparam Block to effectively increase the receptive field, reduce the number of parameters, and improve feature extraction capability. Then, the ADOWN downsampling module is used to mitigate fine-grained information loss, thereby improving the efficiency and performance of the model. Finally, CASPPF (Coordinate Attention-based Spatial Pyramid Pooling Fast) is designed by fusing CA (Coordinate Attention) and SPPF (Spatial Pyramid Pooling Fast), which effectively enhances the feature representation and spatial information integration ability, making the model more accurate and robust when dealing with complex scenes. Experimental results on the AFO dataset show that, compared with the YOLOv8s network, the EMR-YOLO network improves the mAP (mean average precision) and mAP50 by 4.7% and 9.2%, respectively, while reducing the number of parameters and computation by 22.5% and 18.7%, respectively. Overall, the use of UAVs to capture images and deep learning for maritime target recognition for maritime rescue and surveillance improves rescue efficiency and safety.

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Interannual variability of diurnal temperature range in CMIP6 projections and the connection with large-scale circulation - Shuangshuang Wang; Mi Zhang; Jianping Tang; Xiaodong Yan; Congbin Fu; Shuyu Wang (Climate Dynamics, 2024)

Two new sesquiterpene lactones from the branches and leaves of Cinnamomum camphora chvar. Borneol - Zhiyong Xu; Tao Jiang; Wei Xiong; Chuanqi Xie; Yunfei Liu; Xiaodan Han; Xuefang Wen; Jianping Fu; Junwei Xu; Yongsheng Guo; Lei Wu (Phytochemistry Letters, 2024)

Metagenomics and untargeted metabolomics analyses to unravel the formation mechanism of characteristic metabolites in Cantonese soy sauce during different fermentation stages - Linfeng Wen; Jianping Lei; Lixin Yang; Qixin Kan; Peipei Wang; Jun Li; Cong Chen; Liping He; Jiangyan Fu; Chi-Tang Ho; Qingrong Huang; Yong Cao. (Food Research International, 2024)

Transcriptiomics analysis reveals immue regulation and cell death regulation of IFNg in Pelodiscus sinensis STA cells - Jianping Fu; Jun Chen; Xinyan Meng; Zhang Luo; Yi Liu; Lili Wei (Aquaculture, 2023)

Identification and verification of PCDD/Fs indicators from four typical large-scale municipal solid waste incinerations with large sample size in China - Lijun Liu; Xichao Chen; Wenhua Yin; Hao Wu; Junbin Huang; Yanyan Yang; Zhiqiang Gao; Jinqiong Huang; Jianping Fu; Jinglei Han (Waste Management, 2023)

Disruption of intestinal structure, tight junction complex, immune response and microbiota after chronic exposure to copper in swamp eel (Monopterus albus) - Changgao Lin; Jianping Fu; Lin Liu; Hui Wang; Lili Wei (Fish & Shellfish Immunology, 2023)

Critical review on modified floating photocatalysts for emerging contaminants removal from landscape water: problems, methods and mechanism - Xiaoning Fu; Guangzhu Zhou; Jianping Li; Qiuhui Yao; Zuozhen Han; Rongchao Yang; Xi Chen; Yuanhao Wang (Chemosphere, 2023)

Ultralow-background SERS substrates for reliable identification of organic pollutants and degradation intermediates - Longfei Zhang; Rongfang Zhao; Yanzhou Wu; Zhiyang Zhang; Yan Chen; Meichun Liu; Na Zhou; Yunqing Wang; Xiuli Fu; Xuming Zhuang; Jianping Wang; Lingxin Chen (Journal of Hazardous Materials, 2023)

Particle high-speed self-rotation in cyclones with different diameters and application in catalyst deoiling - Qiong Li; Tingting Cheng; Qiqi Li; Junjie Liu; Yanan Liang; Jianping Li; Xia Jiang; Hualin Wang; Pengbo Fu (Journal of Cleaner Production, 2023)

Divergent sensitivity of vegetation to aridity between drylands and humid regions - Guolong Zhang; Yongli He; Jianping Huang; Li Fu; Dongliang Han; Xiaodan Guan; Beidou Zhang (Science of The Total Environment, 2023)

Effects of duct profile parameters on flow characteristics of pump-jet: A numerical analysis on accelerating and decelerating ducts distinguished by cambers and angles of attack - Yunkai Zhou; Giorgio Pavesi; Jianping Yuan; Yanxia Fu; Quanlin Gao (Ocean Engineering, 2023)

Heat waves accelerate the spread of infectious diseases - Xinbo Lian; Jianping Huang; Han Li; Yongli He; Zhi Ouyang; Songbo Fu; Yingjie Zhao; Danfeng Wang; Rui Wang; Xiaodan Guan (Environmental Research, 2023)

ED-DQN: An event-driven deep reinforcement learning control method for multi-zone residential buildings - Qiming Fu; Zhu Li; Zhengkai Ding; Jianping Chen; Jun Luo; Yunzhe Wang; You Lu (Building and Environment, 2023)

Overloading risk assessment of water environment-water resources carrying capacity based on a novel Bayesian methodology - Liting Wang; Weihua Zeng; Ruoxin Cao; Yue Zhuo; Jie Fu; Jianping Wang (Journal of Hydrology, 2023)

Combined transcriptomics and metabolomics analysis reveals lipid metabolic disruption in swamp eel (Monopterus albus) under chronic waterborne copper exposure - Lin Liu; Jianping Fu; Qiongying Tang; Hui Wang; Changgao Lin; Lili Wei (Aquatic Toxicology, 2023)

Identification of Mycobacterium chelonae from Lined Seahorse Hippocampus erectus and Histopathological Analysis - Xiaohui Bai; Shuang Hao; Jianping Fu; Hanchang Sun; Zhang Luo (Fishes, 2023)
The lined seahorse (Hippocampus erectus) is an aquacultural species in China and has important economic and ornamental value. However, the species is affected by disease, which restricts their large-scale cultivation. In 2021, a disease was observed in cultured seahorses in Tianjin, China, with a cumulative mortality rate of 20%. The symptoms observed in the moribund seahorse included a weak swimming capacity, discolored body surface, enlarged liver and kidneys, and numerous white nodules in the parenchymatous organs. The strains HM-2021-1 and HM-2021-2 were isolated from diseased seahorses and were identified as being responsible for the disease. It demonstrated the potential to infect seahorse, and the cumulative mortalities of the seahorses artificially infected with strains HM-2021-1 and HM-2021-2 were 93.3% and 90.0%. The pathogen was identified as Mycobacterium chelonae based on physiological and biochemical tests, and 16S rDNA, rpoB, and Hsp65 gene sequence analysis. To our knowledge, this study is the first report of M. chelonae associated with diseased seahorses in China.

Microcystin-LR-induced autophagy regulates oxidative stress, inflammation, and apoptosis in grass carp ovary cells in vitro - Lili Wei; Jianping Fu; Li He; Hui Wang; Jiming Ruan; Fugui Li; Huadong Wu (Toxicology in Vitro, 2023)

Molecular identification and functional analysis of X-linked inhibitor of apoptosis -associated factor-1 (XAF1) in grass carp, Ctenopharyngodon idella - Jianping Fu; Jun Chen; XinYan Meng; Zhang Luo; Yi Liu; Lili Wei (Fish & Shellfish Immunology, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

An ultrasensitive lateral flow immunoassay platform for foodborne biotoxins and pathogenic bacteria based on carbon-dots embedded mesoporous silicon nanoparticles fluorescent reporter probes - Yuhui Wang; Chen Deng; Sihua Qian; Hui Li; Pan Fu; Hualan Zhou; Jianping Zheng (Food Chemistry, 2023)

Effects of haloxyfop-p-methyl on the developmental toxicity, neurotoxicity, and immunotoxicity in zebrafish - Yi Liu; Jing Guo; Wenjin Liu; Fengjie Yang; Yunyun Deng; Yunlong Meng; Bo Cheng; Jianping Fu; June Zhang; Xinjun Liao; Lili Wei; Huiqiang Lu (Fish & Shellfish Immunology, 2023)

Atomic doping modulates the electronic structure of porous cobalt phosphide nanosheets as efficient hydrogen generation electrocatalysts in wide pH range - Yonglong Wang; Bin Li; Weiping Xiao; Xinping Wang; Yunlei Fu; Zhenjiang Li; Guangrui Xu; Jianping Lai; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2023)

A Review on Hydrodynamic Performance and Design of Pump-Jet: Advances, Challenges and Prospects - Yunkai Zhou; Giorgio Pavesi; Jianping Yuan; Yanxia Fu (Journal of Marine Science and Engineering, 2022)
A pump-jet, which is generally and widely adopted on underwater vehicles for applications from deep sea exploration to mine clearing, consists of a rotor, stator, and duct, with the properties of high critical speed, high propulsion efficiency, great anti-cavitation performance, and low radiated noise. The complex interaction of the flow field between the various components and the high degree of coupling with the appendage result in the requirements of in-depth research on the hydrodynamic performance and flow field for application and design. Due to the initial application on the military field and complicated structure, there is scant literature in the evaluation of pump-jet performance and optimal design. This paper, in a comprehensive and specialized way, summarizes the pump-jet hydrodynamic performance, noise performance, and flow field characteristics involving cavitation erosion and vortices properties of tip-clearance, the interaction between the rotor and the stator and the wake field, as well as the optimal design of the pump-jet. The merits and applications range of numerical and experimental methods are overviewed as well as the design method. It also concludes the main challenges faced in practical applications and proposes a vision for future research. It was found that the compact structure and complex internal and external flow field make the pump-jet significantly different, also leading to higher performance. As the focus of cavitation research, vortices interact with the complex structure of the pump-jet, leading to instabilities of the flow field, such as vibration, radiated noise, and cavitation erosion. The effective approaches are adopted to reduce radiated pump-jet with minimal influence on the hydrodynamic performance, such as eliminating the tip clearance and installing the sawtooth duct. Advanced optimal technology can achieve high performance, cavitation performance, and acoustic performance, possessing good prospects. Further developments in investigation and the application of pump-jets in the multidisciplinary integration of fluid dynamics, acoustics, materials, chemistry, and bionics should be the main focus in future research.

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

The role of sea surface temperature variability in changes to global surface air temperature related to two periods of warming slowdown since 1940 - Yidan Xu; Jianping Li; Haohuan Fu (Climate Dynamics, 2022)

Predisposition to atrioventricular septal defects may be caused by SOX7 variants that impair interaction with GATA4 - Baolei Li; Zhuoyan Li; Jianping Yang; Nanchao Hong; Lihui Jin; Yuejuan Xu; Qihua Fu; Kun Sun; Yu Yu; Yanan Lu; Sun Chen (Molecular Genetics and Genomics, 2022)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

The performance of CORDEX-EA-II simulations in simulating seasonal temperature and elevation-dependent warming over the Tibetan Plateau - Xiaorui Niu; Jianping Tang; Deliang Chen; Shuyu Wang; Tinghai Ou; Congbin Fu (Climate Dynamics, 2021)
To explore the driving mechanisms of elevation-dependent warming (EDW) over the Tibetan Plateau (TP), the output from a suite of numerical experiments with different cumulus parameterization schemes (CPs) under the Coordinated Regional Climate Downscaling Experiments-East Asia (CORDEX-EA-II) project is examined. Results show that all experiments can broadly capture the observed temperature distributions over the TP with consistent cold biases, and the spread in temperature simulations commonly increases with elevation with the maximum located around 4000–5000 m. Such disagreements among the temperature simulations could to a large extent be explained by their spreads in the surface albedo feedback (SAF). All the experiments reproduce the observed EDW below 5000 m in winter but fail to capture the observed EDW above 4500 m in spring. Further analysis suggests that the simulated EDW during winter is mainly caused by the SAF, and the clear-sky downward longwave radiation (LW clr ) plays a secondary role in shaping EDW. The models’ inability in simulating EDW during spring is closely related to the SAF and the surface cloud radiative forcing (CRFs). Furthermore, the magnitude and structure of the simulated EDW are sensitive to the choice of CPs. Different CPs generate diverse snow cover fractions, which can modulate the simulated SAF and its effect on EDW. Also, the CPs show great influence on the LW clr via altering the low-level air temperature. Additionally, the mechanism for different temperature changes among the experiments varies with altitudes during summer and autumn, as the diverse temperature changes appear to be caused by the LW clr for the low altitudes while by the SAF for the middle-high altitudes.

Dynamic processes of the Dora Kamiyama rockslide in the Tibetan Plateau, China: geomorphic implication - Liyong Wang; Zongji Yang; Gang Liu; Shihao Liu; Xiaolong Fu; Jianping Qiao (Bulletin of Engineering Geology and the Environment, 2021)

Correction to: Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2020)

MESP2 variants contribute to conotruncal heart defects by inhibiting cardiac neural crest cell proliferation - Erge Zhang; Jianping Yang; Yang Liu; Nanchao Hong; Huilin Xie; Qihua Fu; Fen Li; Sun Chen; Yu Yu; Kun Sun (Journal of Molecular Medicine, 2020)

On the sensitivity of seasonal and diurnal precipitation to cumulus parameterization over CORDEX-EA-II - Xiaorui Niu; Jianping Tang; Shuyu Wang; Congbin Fu; Deliang Chen (Climate Dynamics, 2020)

Evaluation of the effects of a multiphysics ensemble on the simulation of an extremely hot summer in 2003 over the CORDEX‐EA‐II region - Linyun Yang; Shuyu Wang; Jianping Tang; Xiaorui Niu; Congbin Fu (International Journal of Climatology, 2019)
In this paper, we evaluate a 48‐member multiphysics ensemble using the Weather Research and Forecasting (WRF) model for the JJA extreme precipitation and temperature in 2003 over the CORDEX‐EA‐II domain. The simulated precipitation and temperature are reasonable in the subregions controlled by a large‐scale circulation, yet the biases for both precipitation and temperature are evident over the subregions where the effects of mesoscale processes are important. The performance of various combinations of WRF physical schemes for simulating the JJA precipitation is dependent on the region. Meanwhile, the cumulus and microphysical schemes have substantial influences on the simulation of precipitation, and the land surface models and cumulus schemes play crucial roles in the surface temperature. Our analysis shows that the combination of Noah for the land surface process, Lin for the microphysics, G3D for the cumulus parameterization, and CAM for the radiation scheme can provide the most reliable reproduction of both precipitation and temperature extremes over China. Ensemble analysis shows that the simulated climate extremes are usually accompanied by a large ensemble spread, implying sensitivities to the model physical processes in some subregions. The simulated wind fields at low‐to‐middle atmospheric levels display responses to the options of the land surface models and cumulus schemes. The essential impact of the land–atmospheric interaction on simulating the extremes can be largely attributed to the active convective processes. WRF has difficulties in reproducing the observed temporal evolution of the rainfall process, which consists of continuous large rainfall episodes in the observation data set during the simulation period.

Impact of future land use and land cover change on temperature projections over East Asia - Xiaorui Niu; Jianping Tang; Shuyu Wang; Congbin Fu (Climate Dynamics, 2019)

Transcriptome-based identification of the optimal reference genes as internal controls for quantitative RT-PCR in razor clam (Sinonovacula constricta) - Xuelin Zhao; Jianping Fu; Liting Jiang; Weiwei Zhang; Yina Shao; Chunhua Jin; Jinbo Xiong; Chenghua Li (Genes & Genomics, 2018)

Ensemble evaluation and projection of climate extremes in China using RMIP models - Xiaorui Niu; Shuyu Wang; Jianping Tang; Dong‐Kyou Lee; William Gutowski; Koji Dairaku; John McGregor; Jack Katzfey; Xuejie Gao; Jia Wu; Song‐you Hong; Yuqing Wang; et al. (International Journal of Climatology, 2018)
Under the framework of the Regional Climate Model Intercomparison Project (RMIP III), simulation results from six regional climate models (RCMs) and two global climate models (GCMs) were used to generate climate extreme indices for the present and future over China using two ensemble methods. All the models reasonably captured the observed climate extremes, and performance‐based ensemble averaging (PEA) outperformed the individual model and equal‐weighted averaging (MME) for the control climate. However, noticeable cold deficiencies in temperature extremes were found over areas with complex topography, and too frequent heavy precipitation at smaller intensities was simulated using the multiple model ensembles. Under the A1B scenario for 2041–2060, widespread increases in the 90th percentiles of the maximum temperatures (Tmax90p) and the 10th percentile of the minimum temperatures (Tmin10p) were projected, with larger increases in winter than in summer. Greater intensities in precipitation extremes were projected over China, with the exception of Inner Mongolia. Large uncertainties exist in the projected mean diurnal temperature range (Trange), number of days with precipitation exceeding 10 mm (R10) and the maximum number of consecutive dry days (CDD) because of disagreements in both the magnitudes and signs of the climate model projections, and even the two ensemble methods presented opposite signs over some regions.

Alpha-7 Nicotinic Receptor Signaling Pathway Participates in the Neurogenesis Induced by ChAT-Positive Neurons in the Subventricular Zone - Jianping Wang; Zhengfang Lu; Xiaojie Fu; Di Zhang; Lie Yu; Nan Li; Yufeng Gao; Xianliang Liu; Chunmao Yin; Junji Ke; Liyuan Li; Mengmeng Zhai; et al. (Translational Stroke Research, 2017)

A new maltose-inducible high-performance heterologous expression system in Bacillus subtilis - Jie Yue; Gang Fu; Dawei Zhang; Jianping Wen (Biotechnology Letters, 2017)

Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2016)

Advances in studying interactions between aerosols and monsoon in China - GuoXiong Wu; ZhanQing Li; CongBin Fu; XiaoYe Zhang; RenYi Zhang; RenHe Zhang; TianJun Zhou; JianPing Li; JianDong Li; DeGang Zhou; Liang Wu; LianTong Zhou; et al. (Science China Earth Sciences, 2016)

Whether Metal Element-Containing Herbal Formula Angong Niuhuang Pill Is Safe for Acute Brain Disorders? - Lei Zhao; Fu Peng; Binghe Guan; Xia Li; Wei Wu; Jianping Chen; Jiangang Shen (Biological Trace Element Research, 2015)

Two Different Emission-Wavelength Fluorescent Probes for Aluminum Ion based on Tunable Fluorophores in Aqueous Media - Yanxia Li; Zengchen Liu; Wenping Zhu; Hao Fu; Yongjie Ding; Jianping Xie; Weijie Yang; Lili Li; Chao Cheng (Journal of Fluorescence, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Enhanced extracellular production of α-amylase in Bacillus subtilis by optimization of regulatory elements and over-expression of PrsA lipoprotein - Jingqi Chen; Yuanming Gai; Gang Fu; Wenjuan Zhou; Dawei Zhang; Jianping Wen (Biotechnology Letters, 2015)

Molecular dynamic and quantum mechanics study of drug recognition for the extremity of DNA G-quadruplex groove - Jinlian Li; Jia Fu; Jianping Wang; Donghua Hu; Zhongmin Su; Xiaoqiang Jin (Medicinal Chemistry Research, 2012)

Responses of soil microbial and nematode communities to aluminum toxicity in vegetated oil-shale-waste lands - Yuanhu Shao; Weixin Zhang; Zhanfeng Liu; Yuxin Sun; Dima Chen; Jianping Wu; Lixia Zhou; Hanping Xia; Deborah A. Neher; Shenglei Fu (Ecotoxicology, 2012)

Polyphosphate Deficiency Affects the Sliding Motility and Biofilm Formation of Mycobacterium smegmatis - Tingyu Shi; Tiwei Fu; Jianping Xie (Current Microbiology, 2011)

Comparison of four ensemble methods combining regional climate simulations over Asia - Jinming Feng; Dong-Kyou Lee; Congbin Fu; Jianping Tang; Yasuo Sato; Hisashi Kato; John L. Mcgregor; Kazuo Mabuchi (Meteorology and Atmospheric Physics, 2011)

Surface turbulent flux measurements over the Loess Plateau for a semi-arid climate change study - Jinqing Zuo; Jianping Huang; Jiemin Wang; Wu Zhang; Jianrong Bi; Guoyin Wang; Weijing Li; Peijian Fu (Advances in Atmospheric Sciences, 2009)

An overview of the Semi-arid Climate and Environment Research Observatory over the Loess Plateau - Jianping Huang; Wu Zhang; Jinqing Zuo; Jianrong Bi; Jinsen Shi; Xin Wang; Zhoulin Chang; Zhongwei Huang; Su Yang; Beidou Zhang; Guoyin Wang; Guanghong Feng; et al. (Advances in Atmospheric Sciences, 2008)

Simulation of the radiative effect of black carbon aerosols and the regional climate responses over China - Jian Wu; Weimei Jiang; Congbin Fu; Bingkai Su; Hongnian Liu; Jianping Tang (Advances in Atmospheric Sciences, 2004)